War of nerves chemical warfare from world war I to Al-Qaeda - Tucker, Jonathan B. (Pantheon Books, 2006)
Statesmen, generals, and diplomats have long debated the military utility and morality of chemical warfare. In 1925, the use of chemical weapons in war was prohibited by international treaty; in 1997 the ban on the use of chemical weapons was extended to cover their development, production, and stockpiling. Nevertheless, Iraq employed chemical weapons on a large scale as recently as the 1980s, first during its eight-year war with Iran and then against its rebellious Kurdish minority.